A Comprehensive Exploration of Early Childhood Education (ECE) and Early Childhood Education Centers (ECEC): Shaping the Foundation for Lifelong Learning and Social Interaction - Abdulkareem, Habibat Bolanle (Sekolah Pascasarjana UPI, 2025)
This thorough analysis highlights the essential role of Early Childhood Education Centers (ECECs) in shaping toddlers' social interactions and laying the foundation for lifelong learning. It emphasizes the importance of a supportive and inclusive environment, examining various components such as social activities, skill development, peer interactions, and conflict resolution. Beyond theoretical discussions, the research delves into practical implications for cognitive, emotional, and behavioral development, emphasizing the interconnected nature of these aspects. Additionally, the study explores Early Childhood Education (ECE) with a focus on play-based learning and addresses the evolving role of ECECs in promoting gender inclusivity and quality education. Drawing on Nigerian studies, it investigates gender differences in toddlers' social interactions, providing insights into the impact of early experiences on academic performance. In conclusion, the research advocates for a collaborative and inclusive approach to foster holistic child development, underscoring the crucial role of quality ECECs in shaping future generations. The proposed initiatives aim to prioritize gender equity, inclusivity, and high-quality education in early childhood settings.